Copper-carbon composite current collector, preparation method, negative electrode and lithium-based electrochemical energy storage device

By using a copper-carbon composite liquid formed by combining three-dimensional network carbon groups and copper in the negative electrode of the lithium-ion battery, the problems of lithium dendrites, material powdering and low energy density are solved, and higher energy density, power density and longer service life are achieved.

CN115084537BActive Publication Date: 2025-04-08TSINGHUA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210960969.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-11
Publication Date
2025-04-08
Estimated Expiration
2042-08-11

AI Technical Summary

Technical Problem

The existing lithium batteries and negative electrodes containing lithium capacitors have problems such as lithium dendrites, material powdering and low energy density. The traditional copper foil-based collector has a large weight and cannot effectively improve the energy density.

Method used

The copper-carbon composite liquid collector formed by combining three-dimensional network carbon groups and copper is formed by loading copper on the three-dimensional network carbon groups to form a tight bond, thereby improving the mechanical strength, conductivity and chemical stability of the current collector.

Benefits of technology

Effectively alleviate the formation of dendrite in lithium-ion batteries, accommodate the volume expansion of the negative electrode material, and improve the energy density, power density and life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084537B_ABST
    Figure CN115084537B_ABST
Patent Text Reader

Abstract

The present application relates to the field of material preparation, and provides a copper-carbon composite current collector, a preparation method, a negative electrode, and a lithium-based electrochemical energy storage device, wherein the copper-carbon composite current collector includes a three-dimensional network carbon base and copper loaded on the three-dimensional network carbon base. The present application forms a copper-carbon composite current collector by combining a three-dimensional network carbon base with copper. Based on the characteristics of the three-dimensional network carbon base and the copper base, the copper-carbon composite current collector has the advantages of light weight, high strength, high electrical conductivity, high chemical stability, and easy processing, which can effectively alleviate the formation of dendrites in lithium-ion batteries, accommodate the volume expansion of negative electrode materials, and improve the energy density, power density, and life of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of electrochemical energy storage technology, and specifically, to a copper-carbon composite current collector, a preparation method, a negative electrode, and a lithium-based electrochemical energy storage device. Background Art

[0002] In recent years, lithium batteries and lithium-containing capacitors have achieved tremendous development due to their advantages such as high specific capacity, high voltage, high energy density and no pollution.

[0003] However, the negative electrodes of existing lithium batteries and lithium-containing capacitors have long-term safety issues caused by lithium dendrites. At the same time, the volume expansion and collapse of the negative electrode material due to lithium insertion and migration lead to pulverization, which affects the life of the device. In addition, the negative electrode current collector generally uses a heavy copper foil-based current collector, which is not conducive to improving energy density. Summary of the invention

[0004] The embodiments of the present application provide a copper-carbon composite current collector, a preparation method, a negative electrode and a lithium-based electrochemical energy storage device. The copper-carbon composite current collector formed by combining a three-dimensional network carbon base with copper can not only alleviate the formation of dendrites in lithium-ion batteries, but also accommodate the volume expansion of the negative electrode material, and also improve the energy density, power density and life of the device, thereby effectively solving the problems existing in the prior art.

[0005] A first aspect of an embodiment of the present application provides a copper-carbon composite current collector, comprising a three-dimensional network carbon base and copper supported on the three-dimensional network carbon base.

[0006] Optionally, in the copper-carbon composite current collector, the carbon matrix consists of carbon nanotubes and carbon fibers.

[0007] Optionally, in the copper-carbon composite current collector, the copper covers the surface of the carbon base and the connection points between the carbon bases.

[0008] Optionally, in the copper-carbon composite current collector, the porosity of the carbon base is 80-95%, and the diameter of the macro pores is 0.1-0.5 mm.

[0009] Optionally, in the copper-carbon composite current collector, the mass ratio of copper to carbon base is 1:5 to 1:1.

[0010] Optionally, the copper-carbon composite current collector has a thickness of 0.5 to 2 mm.

[0011] Optionally, the copper-carbon composite current collector has a tensile strength in the length direction of 0.1 to 2 MPa.

[0012] A second aspect of the present application provides a method for preparing a copper-carbon composite current collector, comprising:

[0013] Providing a mixture of carbon fibers and carbon nanotubes;

[0014] After filtering the mixed solution to form an initial carbon-based film, drying is performed to obtain a carbon-based film;

[0015] Plating copper on the connection point between the surface of the carbon-based film and the carbon base to form a composite film;

[0016] The composite film is connected to electrodes, and Joule heat effect is applied in a protective gas atmosphere to obtain a copper-carbon composite current collector.

[0017] Optionally, in the preparation method, providing a mixed solution of carbon fibers and carbon nanotubes comprises:

[0018] The carbon fibers and carbon nanotubes are uniformly dispersed in water to form the mixed solution with a viscosity of 1 to 20 centipoise.

[0019] Optionally, before the drying process, the method further comprises:

[0020] detecting the thickness of the initial carbon-based film;

[0021] The mixed liquid is added to the position of the initial carbon-based film where the average thickness error is more than 5% and then partially filtered.

[0022] A third aspect of an embodiment of the present application provides a negative electrode, comprising the copper-carbon composite current collector as described above, and a negative electrode material filled in the copper-carbon composite current collector.

[0023] A fourth aspect of an embodiment of the present application provides a lithium-based electrochemical energy storage device, comprising the negative electrode as described above.

[0024] Beneficial effects:

[0025] The present application provides a copper-carbon composite current collector, a preparation method, a negative electrode and a lithium-based electrochemical energy storage device. The copper-carbon composite current collector is formed by combining a three-dimensional network carbon base and copper. Based on the characteristics of the three-dimensional network carbon base and the copper base, the copper-carbon composite current collector has the advantages of light weight, high strength, high electrical conductivity, high chemical stability and easy processing. It can effectively alleviate the formation of dendrites in lithium-ion batteries, accommodate the volume expansion of negative electrode materials, and improve the energy density, power density and life of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0027] Figure 1 is a schematic diagram of the structure of a copper-carbon composite current collector proposed in one embodiment of the present application;

[0028] Figure 2 It is a flow chart of a method for preparing a copper-carbon composite current collector proposed in one embodiment of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the prior art can be used. The reagents and other instruments used without specifying the manufacturer are all conventional reagent products that can be purchased commercially.

[0031] In the related art, the negative electrode of lithium electrochemical energy storage devices uses a copper foil-based current collector, which has the defects of low energy density, inability to effectively tolerate the growth of lithium dendrites, and easy pulverization. In response to the above problems, the existing method of using a three-dimensional copper-based current collector can provide a large enough space to tolerate the expansion of negative electrode particles and the growth of lithium dendrites, but it cannot effectively solve the problem of the copper-based current collector being too thick; and the use of a three-dimensional carbon-based current collector can reduce weight, but it is prone to swelling due to liquid absorption, easy deformation, poor mechanical strength, and is not conducive to continuous roll-to-roll processing. Therefore, the existing current collector has the problem of not being able to have high mechanical strength, high energy density, and effective tolerance of lithium dendrite growth.

[0032] In view of this, the embodiments of the present application propose a copper-carbon composite current collector and its preparation method, a negative electrode, and an electrochemical energy storage device. The copper-carbon composite current collector formed by the combination of a three-dimensional network carbon base and copper can not only alleviate the formation of dendrites in lithium-ion batteries, but also accommodate the volume expansion of the negative electrode material, and also improve the energy density, power density and life of the device, effectively solving the problems existing in the prior art.

[0033] In a first aspect, an embodiment of the present application provides a copper-carbon composite current collector, such as Figure 1 As shown, a schematic diagram of the structure of the copper-carbon composite current collector in an embodiment of the present application is shown. Figure 1 As shown, the copper-carbon composite current collector includes a three-dimensional network carbon base 11 and copper 12 supported on the three-dimensional network carbon base.

[0034] The copper-carbon composite current collector is composed of copper and a three-dimensional network carbon base, and the copper is loaded on the three-dimensional network carbon base structure. Among them, the three-dimensional network carbon base has a low density, so that the copper-carbon composite current collector is lighter than the copper-based current collector; the three-dimensional network carbon base has a large number of pore structures, which can not only further reduce the overall weight of the current collector, but also the pore structure is conducive to alleviating the formation of dendrites in lithium-ion batteries, and can also accommodate the volume expansion of negative electrode materials; and the presence of copper is conducive to improving mechanical strength and chemical stability, and also makes the current collector The conductivity is higher; therefore, when the copper-carbon composite current collector is used as the negative electrode material in the electrochemical energy storage device, the device energy density, power density and service life can be significantly improved.

[0035] In the copper-carbon composite current collector provided in the embodiment of the present application, copper can be loaded on the carbon base by evaporation or electroplating. Optionally, copper is covered on the surface of the carbon base and the connection points between the carbon bases, and copper and the carbon-based structural material can be closely combined under the premise of ensuring that the current collector is in a three-dimensional porous state as a whole, thereby effectively improving the mechanical strength and conductivity of the current collector by using the copper metal phase.

[0036] Among them, under the joint action of the three-dimensional network structure carbon base and the loaded copper, the tensile strength of the above copper-carbon composite current collector in the length direction can reach 0.1 to 2 MPa.

[0037] In the copper-carbon composite current collector provided in the embodiment of the present application, copper is uniformly loaded on the three-dimensional network carbon-based structure, so that the overall structural strength is consistent, and copper and carbon-based structural materials can form a more tightly combined body. Optionally, in the copper-carbon composite current collector, the mass ratio of copper to carbon-based is 1:5 to 1:1.

[0038] Optionally, in the embodiment of the present application, the carbon base is composed of carbon nanotubes and carbon fibers. Among them, carbon nanotubes have high modulus, high strength and good flexibility, and can withstand large tensile loads. At the same time, the one-dimensional conductive properties of carbon nanotubes are conducive to reducing the resistance of the network carbon-based structure formed; while carbon fibers have the characteristics of high temperature resistance, friction resistance, heat conduction and corrosion resistance, and have high strength and modulus along the fiber axis. In addition, carbon fibers have a low density and high specific strength and specific modulus, and are suitable for being used as a reinforcing material for compounding with resins, metals, ceramics and carbon, etc., which provides a guarantee for the mechanical properties and processing properties of the network carbon-based structure formed.

[0039] In the copper-carbon composite current collector provided in the embodiment of the present application, a small amount of carbon nanotubes can have a good effect on conductivity, and the main body is carbon fiber, which is more advantageous for strength and processability. Optionally, in the copper-carbon composite current collector provided in the embodiment of the present application, the mass ratio of carbon nanotubes to carbon fiber is 5:95 to 50:50.

[0040] Specifically, in the copper-carbon composite current collector provided in the embodiment of the present application, the carbon-based porosity of the three-dimensional network structure is 80-95%, and the diameter of the macroscopic pores is 0.1-0.5 mm. Among them, the pore structure allows the battery active material to be filled therein. The greater the porosity, the more fillers can be made, and the smaller the proportion of materials that do not contribute to the capacity. The pore diameter needs to be within a certain range, which not only meets the porosity requirements, but also does not cause the network structure to collapse. Among them, if the pore size is too large, it is easy to affect the structural strength due to structural imbalance, while if the pore size is too small, it is not convenient for the active material to be filled and affects the ion transport characteristics.

[0041] The thickness of the copper-carbon composite current collector provided in the present application can be controlled by the preparation method.

[0042] Optionally, in one embodiment, the copper-carbon composite current collector provided in the embodiment of the present application has a thickness of 0.5-2 mm, so as to load more active materials based on the above-mentioned porosity and pore size; the copper-carbon composite current collector at the original thickness can be compressed into a compact film of 0.05-0.4 mm to reduce internal resistance, better match device installation, and facilitate the overall small size of the device. Among them, the copper-carbon composite current collector at the original thickness can be compressed to 0.07-0.4 mm after filling the electrode material.

[0043] The copper-carbon composite current collector provided in the present application can be wound up, and its length is 5 to 500 m, which is convenient for continuous roll-to-roll processing and production.

[0044] The second aspect of the embodiment of the present application provides a method for preparing a copper-carbon composite current collector, which is used to prepare the copper-carbon composite current collector described in the first aspect. Figure 2 A flow chart of a method for preparing a copper-carbon composite current collector is shown, such as Figure 2 As shown, the following steps are included:

[0045] S101, providing a mixture of carbon fibers and carbon nanotubes.

[0046] In specific implementation, carbon fibers and carbon nanotubes are uniformly dispersed in a solvent such as water according to a preset ratio to form the above-mentioned mixed solution. The carbon fibers and carbon nanotubes can be uniformly dispersed by mechanical stirring or magnetic stirring to form a mixed solution with a viscosity of 1 to 20 centipoise.

[0047] In some embodiments, the ratio of carbon fibers to carbon nanotubes is 5:95 to 50:50.

[0048] S102, filtering the mixed solution to form an initial carbon-based film, and then drying the mixed solution to obtain a carbon-based film.

[0049] In specific implementation, the mixture is poured evenly onto a continuously moving filter through a porous tube distributor, so that the mixed liquid can be evenly dispersed on the filtering surface of the filter after flowing out, forming the initial form of the carbon-based film, and then dried to remove the remaining solvent components in the mixed liquid to form a carbon-based film.

[0050] In some embodiments, when the mixed solution is poured onto the filter through the porous tube distributor, the moving speed of the filter is controlled to be 1-100 mm / s.

[0051] In some embodiments, when the initial form of the carbon-based film is formed, natural filtration is first performed and then vacuum filtration is performed to ensure that the surface of the film is smooth. Optionally, the natural filtration time is 10 to 20 minutes and the vacuum filtration time is 5 to 30 seconds.

[0052] In some embodiments, the drying step is: firstly vacuum filtration the initial carbon-based film at room temperature to remove 90-99% of the water; and then vacuum filtration is performed under heating to remove 99.5-99.9% of the water. Optionally, in this step, the vacuum filtration time at room temperature is 30-40 minutes, and the temperature of the heated vacuum filtration is 100-130°C and the time is 10-15 minutes.

[0053] In some embodiments, before the drying process is performed, the method for preparing the copper-carbon composite current collector provided in the embodiment of the present application further includes:

[0054] detecting the thickness of the initial carbon-based film;

[0055] The mixed liquid is added to the position of the initial carbon-based film where the average thickness error is more than 5% and then partially filtered.

[0056] In the above embodiment, after the initial carbon-based film is formed on the filter, the thickness of the film is detected by a thickness detector, and the mixed liquid of the carbon fibers and carbon nanotubes is controlled to be added to the film position where the average thickness error is less than 5% to fill the film thickness at that location and keep the overall thickness consistent. The location where the controlled added mixed liquid is added is then locally filtered by natural filtration and vacuum filtration to form an initial carbon-based film with consistent thickness.

[0057] S103, plating copper on the connection points between the surface of the carbon-based film and the carbon base to form a composite film.

[0058] In this step, metal copper is plated on the surface of the carbon-based film and / or the connection points between the carbon bases by electroplating or evaporation.

[0059] In a specific implementation, the film can be continuously passed through an evaporation machine to evaporate copper on the surface and nodes of the carbon film. Optionally, the moving speed of the film is controlled to be 2 m / min.

[0060] S104, connecting the composite film to electrodes, and applying Joule heating effect in a protective gas atmosphere to obtain a copper-carbon composite current collector.

[0061] In this step, the protective gas atmosphere can prevent oxidation of elements such as copper in the composite film due to Joule heat effect; the protective gas atmosphere can specifically be a nitrogen atmosphere or an argon atmosphere.

[0062] In the specific implementation, the composite film is connected to the electrode, and the Joule heating effect is continuously applied for a preset time in a nitrogen atmosphere to make the copper and carbon tightly bonded, and then the power is turned off, the film is cooled to room temperature in nitrogen, and then rolled up to obtain the product. Among them, the time for applying the Joule heating effect can be set to 10s.

[0063] In some embodiments, the final product includes the following features:

[0064] A three-dimensional mesh film material is formed by filtering carbon nanotubes and carbon fibers, and then copper is electroplated or evaporated, and then heated and welded by electricity to form a copper-carbon composite current collector. Based on the three-dimensional mesh carbon-based and copper-based characteristics, the copper-carbon composite current collector has the advantages of light weight, high strength, high electrical conductivity, high chemical stability and easy processing. It can effectively alleviate the formation of dendrites in lithium-ion batteries, accommodate the volume expansion of negative electrode materials, and improve the energy density, power density and life of the device.

[0065] The third aspect of the embodiment of the present application provides a negative electrode, including the copper-carbon composite current collector as described above, and a negative electrode material filled in the copper-carbon composite current collector. The negative electrode is suitable for being used as a negative electrode of an electrochemical energy storage device containing lithium elements. The negative electrode material is filled in the gap of the current collector, and the structure of the composite negative electrode and the current collector is formed by pressing.

[0066] A fourth aspect of the embodiments of the present application provides a lithium-based electrochemical energy storage device, comprising the negative electrode as described above.

[0067] The above-mentioned lithium-based electrochemical energy storage device can be a lithium battery or a lithium-containing capacitor; specifically, the above-mentioned electrochemical energy storage device can be a lithium ion battery, a lithium metal battery, a lithium sulfur battery, a solid-state battery, a lithium ion capacitor, a battery-type capacitor and other hybrid capacitors.

[0068] The present application provides a copper-carbon composite current collector and a preparation method thereof, a negative electrode, and a lithium-based electrochemical energy storage device. The copper-carbon composite current collector formed by combining a three-dimensional network carbon base with a copper foil can have both three-dimensional network carbon base and copper base characteristics, and has the following advantages:

[0069] (1) Compared with the all-copper-based three-dimensional current collector, the weight is reduced by 50-80%, which can correspondingly increase the energy density of the device by 3-5%.

[0070] (2) Compared with all-carbon-based three-dimensional current collectors, the mechanical strength is increased by 100-200%, which can meet the requirements of continuous and rapid roll-to-roll processing, increase the device preparation efficiency by 50%, and reduce the preparation cost by 5-10%.

[0071] (3) Compared with copper foil current collector, the weight is reduced by 20-50%, which can correspondingly increase the energy density of the device by 1-3%.

[0072] (4) Due to tolerance of dendrite growth and pulverization of negative electrode materials, the device life can be increased by 30-50% compared with the device using copper foil current collector.

[0073] (5) It is easier to weld the pole ears than the all-carbon-based three-dimensional current collector, and the contact resistance is 50-90% lower, which can increase the power density by 40-70%.

[0074] In order to enable those skilled in the art to more clearly understand the present application, the copper-carbon composite current collector and the preparation method thereof described in the present application are now described in detail through the following examples.

[0075] Example 1

[0076] The copper-carbon composite current collector provided in this embodiment is composed of a three-dimensional network carbon-based material and copper covering the surface and connection nodes of the carbon-based material. The three-dimensional network carbon-based material is composed of carbon nanotubes and carbon fibers, and has a porosity of 80% and a macroscopic pore diameter of 0.1 mm.

[0077] In the copper-carbon composite current collector, copper and carbon-based materials form a close combination, and the mass ratio of copper to carbon is 1:1; the copper-carbon composite current collector has a thickness of 2 mm and can be compressed into a compact film of 0.4 mm. After filling with electrode materials, it can be compressed to 0.4 mm, with a length of 500 m and a tensile strength of 2 MPa in the length direction.

[0078] The negative electrode material is filled into the gap of the current collector, and a composite negative electrode and current collector structure is formed by pressing.

[0079] This embodiment also provides a method for preparing the copper-carbon composite current collector, comprising:

[0080] (1) Carbon fibers and carbon nanotubes were uniformly dispersed in water at a mass ratio of 95:5 to form a mixed solution with a viscosity of 1 centipoise.

[0081] (2) The mixed solution is evenly poured onto a continuously moving filter through a porous tube distributor, and the speed of the membrane movement is controlled to be 100 mm / s. The initial carbon-based membrane is then obtained by natural filtration for 20 minutes and vacuum filtration for 30 seconds.

[0082] (3) The thickness of the initial carbon-based film is measured by a thickness detector. For locations where the average thickness error is less than 5%, controlled liquid replenishment and local filtration are performed.

[0083] (4) The initial carbon-based film after rehydration was subjected to vacuum filtration at room temperature for 40 minutes to remove 99% of the water; then, it was heated and vacuum filtered at 100° C. for 15 minutes to remove 99.5% of the water to obtain a carbon-based film.

[0084] (5) The carbon-based film is continuously passed through a vapor deposition machine, the moving speed of the film is controlled to be 2 m / min, and copper is vapor deposited on the surface of the carbon film and at the connection nodes to form a composite film.

[0085] (6) Connecting the evaporated composite film to the electrode, continuously applying Joule heating effect for 10 seconds in a nitrogen atmosphere to achieve a tight bond between copper and carbon, then turning off the power supply, allowing the film to cool to room temperature in nitrogen, and then rolling it up to form a copper-carbon composite current collector.

[0086] After comparative testing, the copper-carbon composite current collector provided in this embodiment has a 50% weight reduction compared with the all-copper-based three-dimensional current collector, which can correspondingly increase the energy density of the device by 3%; compared with the all-carbon-based three-dimensional current collector, the mechanical strength of the copper-carbon composite current collector is increased by 200%, which can meet the requirements of continuous and rapid roll-to-roll processing, increase the device preparation efficiency by 50%, and reduce the preparation cost by 10%. Compared with the copper foil current collector, the weight is reduced by 50%, which can correspondingly increase the energy density of the device by 3%. Due to the tolerance of dendrite growth and the tolerance of pulverization of negative electrode materials, the copper-carbon composite current collector has a 50% longer device life than the copper foil current collector; the copper-carbon composite current collector is easier to weld the pole ear than the all-carbon-based three-dimensional current collector, and the contact resistance is 50% lower, which can increase the power density by 40%.

[0087] Example 2

[0088] The copper-carbon composite current collector provided in this embodiment is composed of a three-dimensional network carbon-based material and copper covering the surface and connection nodes of the carbon-based material. The three-dimensional network carbon-based material is composed of carbon nanotubes and carbon fibers, and has a porosity of 95% and a macroscopic pore diameter of 0.5 mm.

[0089] In the copper-carbon composite current collector, copper and carbon-based materials form a close combination, and the mass ratio of copper to carbon is 1:5; the copper-carbon composite current collector has a thickness of 0.5 mm and can be compressed into a compact film of 0.05 mm. After filling with electrode materials, it can be compressed to 0.07 mm, with a length of 5 m and a tensile strength of 0.1 MPa in the length direction.

[0090] The negative electrode material is filled into the gap of the current collector, and a composite negative electrode and current collector structure is formed by pressing.

[0091] This embodiment provides a method for preparing the copper-carbon composite current collector, comprising:

[0092] (1) Carbon fibers and carbon nanotubes were uniformly dispersed in water at a mass ratio of 50:50 to form a mixed solution with a viscosity of 20 centipoise.

[0093] (2) The mixed solution is evenly poured onto a continuously moving filter through a porous tube distributor, the moving speed of the membrane is controlled to be 1 mm / s, and then filtered naturally for 20 minutes and vacuum filtered for 5 seconds to obtain an initial carbon-based membrane.

[0094] (3) The thickness of the initial carbon-based film is measured by a thickness detector. For locations where the average thickness error is less than 5%, controlled liquid replenishment and local filtration are performed.

[0095] (4) The initial carbon-based film after rehydration was subjected to vacuum filtration at room temperature for 30 minutes to remove 99% of the water; then, it was heated and vacuum filtered at 130° C. for 10 minutes to remove 99.9% of the water to obtain a carbon-based film.

[0096] (5) The carbon-based film is continuously passed through a vapor deposition machine, the moving speed of the film is controlled to be 0.5 m / min, and copper is vapor-deposited on the surface of the carbon film and at the connection nodes to form a composite film.

[0097] (6) Connecting the evaporated composite film to the electrode, continuously applying Joule heating effect for 5 seconds in a nitrogen atmosphere to achieve a tight bond between copper and carbon, then turning off the power supply, allowing the film to cool to room temperature in nitrogen, and then rolling it up to form a copper-carbon composite current collector.

[0098] After comparative tests, the copper-carbon composite current collector provided in this embodiment has a weight reduction of 80% compared with the all-copper-based three-dimensional current collector, which can correspondingly increase the energy density of the device by 5%; compared with the all-carbon-based three-dimensional current collector, the mechanical strength of the above copper-carbon composite current collector is increased by 100%, which can meet the requirements of continuous and rapid roll-to-roll processing, so that the device preparation efficiency is increased by 50%, and the preparation cost is reduced by 5%; compared with the copper foil current collector, the weight is reduced by 20%, which can correspondingly increase the energy density of the device by 1%. Due to tolerance of dendrite growth and tolerance of pulverization of negative electrode materials, the above copper-carbon composite current collector can increase the device life by 30% compared with the use of copper foil current collector; the above copper-carbon composite current collector is easier to weld the pole ears than the all-carbon-based three-dimensional current collector, and the contact resistance is 90% lower, which can increase the power density by 70%.

[0099] Example 3

[0100] The copper-carbon composite current collector provided in this embodiment is composed of a three-dimensional network carbon-based material and copper covering the surface and connection nodes of the carbon-based material. The three-dimensional network carbon-based material is composed of carbon nanotubes and carbon fibers, and has a porosity of 90% and a macroscopic pore diameter of 0.3 mm.

[0101] In the copper-carbon composite current collector, copper and carbon-based materials form a close combination, and the mass ratio of copper to carbon is 1:3; the copper-carbon composite current collector has a thickness of 1 mm and can be compressed into a compact film of 0.1 mm. After filling with electrode materials, it can be compressed to 0.12 mm, with a length of 50 m and a tensile strength of 0.5 MPa in the length direction.

[0102] The negative electrode material is filled into the gap of the current collector, and a composite negative electrode and current collector structure is formed by pressing.

[0103] This embodiment also provides a method for preparing the copper-carbon composite current collector, comprising:

[0104] (1) Carbon fibers and carbon nanotubes were uniformly dispersed in water at a mass ratio of 75:25 to form a mixed solution with a viscosity of 10 centipoise.

[0105] (2) The mixed solution is evenly poured onto a continuously moving filter through a porous tube distributor, and the speed of the membrane movement is controlled to be 10 mm / s. The initial carbon-based membrane is then obtained by natural filtration for 20 minutes and vacuum filtration for 15 seconds.

[0106] (3) The thickness of the initial carbon-based film is measured by a thickness detector. For locations where the average thickness error is less than 5%, controlled liquid replenishment and local filtration are performed.

[0107] (4) The initial carbon-based film after rehydration was subjected to vacuum filtration at room temperature for 35 minutes to remove 99% of the water; then, it was heated and vacuum filtered at 120° C. for 15 minutes to remove 99.9% of the water to obtain a carbon-based film.

[0108] (5) The carbon-based film is continuously passed through a vapor deposition machine, the moving speed of the film is controlled to be 1 m / min, and copper is evaporated on the surface of the carbon film and at the connection nodes to form a composite film.

[0109] (6) Connecting the evaporated composite film to the electrode, continuously applying Joule heating effect for 10 seconds in a nitrogen atmosphere to achieve a tight bond between copper and carbon, then turning off the power supply, allowing the film to cool to room temperature in nitrogen, and then rolling it up to form a copper-carbon composite current collector.

[0110] After comparative testing, the copper-carbon composite current collector provided in this embodiment has a 70% weight reduction compared with the all-copper-based three-dimensional current collector, which can correspondingly increase the energy density of the device by 4%; compared with the all-carbon-based three-dimensional current collector, the mechanical strength of the copper-carbon composite current collector is increased by 150%, which can meet the requirements of continuous and rapid roll-to-roll processing, increase the device preparation efficiency by 50%, and reduce the preparation cost by 7%. Compared with the copper foil current collector, the weight is reduced by 30%, which can correspondingly increase the energy density of the device by 2%. Due to the tolerance of dendrite growth and the tolerance of pulverization of negative electrode materials, the copper-carbon composite current collector has a 40% longer device life than the copper foil current collector; the copper-carbon composite current collector is easier to weld the pole ear than the all-carbon-based three-dimensional current collector, and the contact resistance is 80% lower, which can increase the power density by 60%.

[0111] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0112] The technical solution provided by the present application is described in detail above. The principle and implementation method of the present application are described in this article using specific examples. The description of the above embodiments is only used to help understand the present application, and the content of this specification should not be understood as limiting the present application. At the same time, for those of ordinary skill in the art, according to the present application, there will be different forms of changes in the specific implementation methods and application scopes. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present application.

Claims

1. A copper-carbon composite current collector, characterized in that: It includes a three-dimensional carbon network base and copper supported on the three-dimensional carbon network base; The carbon matrix is ​​composed of carbon nanotubes and carbon fibers; the mass ratio of the carbon nanotubes to the carbon fibers is 5:95 to 50:50; The mass ratio of the copper to the carbon base is 1:5 to 1:

1.

2. The copper-carbon composite current collector according to claim 1, characterized in that: The copper covers the surfaces of the carbon groups and the connection points between the carbon groups.

3. The copper-carbon composite current collector according to claim 1, characterized in that: The porosity of the carbon base is 80-95%, and the diameter of the macro pores is 0.1-0.5 mm.

4. A method for preparing the copper-carbon composite current collector according to any one of claims 1 to 3, characterized in that: The steps include: Providing a mixture of carbon fibers and carbon nanotubes; After filtering the mixed solution to form an initial carbon-based film, drying is performed to obtain a carbon-based film; Plating copper on the connection points between the surface of the carbon-based film and the carbon base to form a composite film; The composite film is connected to electrodes, and Joule heat effect is applied in a protective gas atmosphere to obtain a copper-carbon composite current collector.

5. The preparation method according to claim 4, characterized in that: The method of providing a mixed solution of carbon fibers and carbon nanotubes comprises: The carbon fibers and carbon nanotubes are uniformly dispersed in water to form the mixed solution with a viscosity of 1 to 20 centipoise.

6. The preparation method according to claim 5, characterized in that: Before the drying process, the method further comprises: detecting the thickness of the initial carbon-based film; The mixed liquid is added to the position of the initial carbon-based film where the average thickness error is more than 5% and local filtering is performed.

7. A negative electrode, characterized in that It comprises the copper-carbon composite current collector as claimed in any one of claims 1 to 3, and a negative electrode material filled in the copper-carbon composite current collector.

8. A lithium-based electrochemical energy storage device, characterized in that: Comprising the negative electrode as claimed in claim 7.

Citation Information

Patent Citations

  • Carbon nanotube paper-metal or alloy composite current collector and preparation method thereof

    CN108134093A

  • Composite lithium metal negative electrode current collector as well as preparation method and application thereof

    CN112768697A